Pengembangan Media Pembelajaran Pop-Up Book Materi Karakteristik Ruang dan Pemanfaatan Sumber Daya Alam untuk Kesejahteraan Masyarakat Kelas IV SD - Norhayati Norhayati; Risdiana Andika Fatmawati; Muhammad Aqmal Nurcahyo (Jurnal Edukasi, 2023)
This study aims to develop Pop Up Book learning media that can be used as a varied learning medium for grade IV Elementary Schools. The research method used is the Research and Development (R&D) model used, namely the Borg and Gall model carried out in seven stages, namely Research and Information collection, Planning, Develop Preliminary form of Product, Preliminary Field Testing, Main Product Revision, Main Field Testing, Operational Product Revision. Data collection techniques, researchers used feasibility questionnaires and practicality questionnaires. The instrument uses a validation sheet and a questionnaire sheet.The results showed that the score obtained from the validation of media experts got a score of 80% in the feasible category, material validation obtained a score of 80% in the feasible category. The initial field trials of the students' responses were 75% in the practical category, the main field trials of the students' responses obtained a score of 76% in the practical category, the teacher's response obtained a score of 91% in the very practical category.